Evaluation of the possibility of detecting cracks during the control of luminescence on turbine blades after application of complex heat-resistant coatings - Konstantin Balushok; Oleksandr Seliverstov; Oleksandr Prokopenko; Sergii Sakhno (Авіаційно-космічна техніка та технологія)
Currently, gas turbine engines (GTD) are being improved and made more powerful by increasing the temperature of the gases in front of the turbine and increasing the air compression ratio in the compressor. In the aviation industry, nickel heat-resistant alloys such as ЖС6У-ВІ, ЖС26-ВІ, ЖС32-ВІ, etc. are used to manufacture GTD blades. Despite their high properties in terms of corrosion resistance and heat resistance, the service life of GTD blades and their protection against oxidation and corrosion damage is ensured by applying coatings using various technologies both to the flowing surface of the blade blades (heat-resistant and heat-protective) and to the inner surfaces of the cooled channels (diffusion coatings). Failure of turbine blades is one of the most severe types of damage to turbine blades, so at different stages of serial production, including after applying heat-resistant coatings, LUM1-OV inspection of blades is performed to detect cracks that can form during processing and lead to their failure during engine operation. The paper evaluates the possibility of detecting cracks on GTD turbine blades with complex heat-resistant coatings GCP+SDP-2. The study was carried out on samples of working blades in the form of an experiment. First, fatigue tests of the samples were carried out on a test bench until cracks appeared. Then, a complex heat-resistant coating of GCP (CrAl gas circulation coating) + SDP-2 (heat-resistant alloy of the Ni-Cr-Al-Y system) was applied to the blade profile in stages according to the serial technology. After each coating was applied, the blades were inspected by the LUM1-OV method to determine the possibility of crack detection. The results showed that immediately after the application of the complex heat-resistant coating, cracks on the blades were not detected, because they spread only in the GCP layer and partially pass into the SDP-2 layer without reaching the surface. The results obtained can be the basis for removing the luminescent inspection operation from the technological process, immediately after applying complex heat-resistant coatings. Since this does not allow detecting cracks in the blade material and can lead to unnecessary costs for additional technological operations.